Bi-polymer electrospun nanofibers embedding ag3 po4 /p25 composite for efficient photocatalytic degradation and anti-microbial activity - Habib, Zunaira; Lee, Chang Gu; Li, Qilin; Khan, Sher Jamal; Ahmad, Nasir Mahmood; Jamal, Yousuf; Huang, Xiaochuan; Javed, Hassan (Catalysts, 2020)
Using a bi-polymer system comprising of transparent poly(methyl methacrylate) (PMMA) and poly(vinyl pyrrolidone) (PVP), a visible light active Ag3 PO4 /P25 composite was immobilized into the mats of polymeric electrospun nanofibers. After nanofibers synthesis, sacrificial PVP was removed, leaving behind rough surface nanofibers with easy access to Ag3 PO4 /P25 composite. The remarkable photocatalytic efficiency was attained using a PMMA and Ag3 PO4 /P25 weight ratio of 1:0.6. Methyl orange (MO) was used to visualize pollutant removal and exhibited stable removal kinetics up to five consecutive cycles under simulated daylight. Also, these polymeric nanofibers (NFs) revealed an important role in the destruction of microorganisms (E. coli), signifying their potential in water purification. A thin film fibrous mat was also used in a small bench scale plug flow reactor (PFR) for polishing of synthetic secondary effluent and the effects of inorganic salts were studied upon photocatalytic degradation in terms of total organic carbon (TOC) and turbidity removal. Lower flow rate (5 mL/h) resulted in maximum TOC and turbidity removal rates of 86% and 50%, respectively. Accordingly, effective Ag3 PO4 /P25 immobilization into an ideal support material and selectivity towards target pollutants could both enhance the efficiency of photocatalytic process under solar radiations without massive energy input.
Keywords: Ag3 PO4 /P25; Escherichia coli; Inorganic salts; Methyl orange; Nanofibers; Photocatalytic degradation; Plug flow reactor